The Effect of Housing Circumstances on Recidivism: Evidence From a Sample of People on Probation in San Francisco - Jacobs, Leah A. (Criminal justice and behavior, 2020)
The relationships between housing circumstances and recidivism are well established among people released from prison. Despite probation being far more common than prison or parole, we know little about living situations, homelessness, and residential instability among people on probation, and we know even less regarding how these housing circumstances may affect their risk of recidivism. Using a unique dataset of 2,453 people on probation and longitudinal analyses, this study finds that housing insecurity is common and is associated with an increased risk of recidivism among people on probation, above and beyond an array of other recidivism risk factors. Furthermore, we find housing effects are particularly strong for relatively low risk people and for relatively low-severity offenses (i.e., property crimes, minor crimes, and revocations). Interventions that increase housing access for people on probation may reduce recidivism, especially for those who are relatively low risk and low-level reoffending.